THE IMPACT OF PRICE PERCEPTION AND BRAND IMAGE ON ATTITUDINAL LOYALTY OF INNISFREE SKINCARE CONSUMERS - Halim, Michelle (Journal of International Conference Proceedings, 2023)
Price perception and brand image are considered as two prominent factors that influence..consumers..intention..to..buy…a skincare. However, those factors do not guarantee consumers’ commitment to a brand. Makes the Innisfree as the research context, researchers want to study whether price..perception..and..brand..image..affect attitudinal loyalty. This research reconstructs the research model of Adawiah (2015) by adding attitudinal loyalty as an endogenous construct and using price perception and brand image as an exogenous construct. The object of this study is Innisfree Skincare. Data..was..collected..by.distributing.google forms.to 150 respondents using purposive sampling. The..data..analysis..technique used..is..Structural.Equation.Modeling.with WarpPLS.7.0. Research shows that..price.perception..and...brand….image have a positive and significant effect on the attitudinal loyalty of Innisfree consumers. Companies are advised to reduce purchase costs, add variants for acne-prone skin, and increase Innisfree’s…advantage….over competitors. Researchers are advised to discuss the effect of..price.perception..on brand..image..and add behavioral loyalty as an endogenous construct.